2008
DOI: 10.1080/00173130802513784
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network models of relationships betweenCladosporiumspores and meteorological factors in Szczecin (Poland)

Abstract: Moulds are common aeroallergens and Cladosporium is considered to be one of the more prevalent examples of these. Aiming to reduce the risk for allergic individuals, we constructed predictive models for the fungal spore circulation in Szczecin, Poland. Monthly forecasting models were developed for the airborne spore concentrations of Cladosporium, the most abundant fungal taxa in the area. Aerobiological sampling was conducted over 2004-2007, using a Lanzoni trap. Simultaneously, the following meteorological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…(Grinn-Gofroń and Strzelczak 2008a ; Astray et al 2010 ; Kumar et al 2013 ), Cladosporium spp. (Grinn-Gofroń and Strzelczak 2008b ), and to some extent also for Ganoderma spp. (Kasprzyk et al 2011 ; Sadyś et al 2016 ).…”
Section: Introductionmentioning
confidence: 98%
“…(Grinn-Gofroń and Strzelczak 2008a ; Astray et al 2010 ; Kumar et al 2013 ), Cladosporium spp. (Grinn-Gofroń and Strzelczak 2008b ), and to some extent also for Ganoderma spp. (Kasprzyk et al 2011 ; Sadyś et al 2016 ).…”
Section: Introductionmentioning
confidence: 98%
“…Most of these studies were based on simple descriptive statistics, such as Pearson or Spearman’s correlation coefficients, or on multiple technique, such as the Duncan multiple range test and multiple regression model (Katial et al 1997 ; Angulo-Romero et al 1999 ; Mitakakis et al 2001 ; Troutt and Levetin 2001 ; Stennett and Beggs 2004 ). For the three types of spores ( Alternaria , Cladosporium and Ganoderma ), the predictive models were developed using advanced statistical methods like: artificial neural networks (ANN) and multivariate regression trees (MRT) (Grinn-Gofroń and Strzelczak 2008a , 2008b , 2009 , 2011 ). All these studies put emphasis on the statistical analysis of the correlation between the level of concentration of particular fungal spore types and weather parameters, however do not examine the complex composition of spores and its dependence on meteorological factors.…”
Section: Introductionmentioning
confidence: 99%
“…In Szczecin, there have been few studies on atmospheric mycobionta. Aeromycological research in outdoor environments has been carried out in Szczecin only for selected allergenic taxa (Alternaria, Cladosporium, Ganoderma, Didymella) [1][2][3][4]. The main goal of this study was to create a spore calendar for 2013 and show the percentage of all identified fungal spores.…”
Section: Introductionmentioning
confidence: 99%